Avaliação dos parâmetros inflamatórios e patológicos no modelo experimental de encefalopatia hepática em camundongos deficientes para TNFR1 - Rafaela Pinto Coelho Santos (2024)
Hepatic encephalopathy (HE) is a potentially reversible neuropsychiatric syndrome, with a significant contribution by neuroinflammation, neuronal death, and neurotransmitter dysregulation in associated neuropsychiatric symptoms. It is well-known that tumor necrosis factor (TNF) plays an important role in the development and progression of HE; however, its role is not yet completely understood, especially in the earlier stages of this syndrome. Experimental rodent models have been used to investigate the underlying mechanisms and potential therapeutic targets for HE. This study aimed to evaluate hepatic and cerebral histopathology, locomotor activity, and memory in wild-type (WT) mice during experimental HE induced by acute liver injury (ALI) due to thioacetamide (TAA) administration. Additionally, locomotor activity and neuroinflammation were analyzed in mice lacking the TNF receptor 1 (TNFR1-/-) with TAA-induced HE. For behavioral and histopathological analyses, female C57BL/6 mice received TAA or saline intraperitoneally (i.p.). Locomotor activity was accessed on the 1st, 3rd, and 7th day post-induction (d.p.i.) of HE. Memory assessment included novel object recognition and Y-maze tests up to 8th day, and the Barnes maze test until the 13th d.p.i. Liver and brain tissues were collected for histopathological analysis on the 7th d.p.i. HE was associated with locomotor deficits only on the 1st d.p.i., and cognitive impairment in the open field test in repeated exposures; no changes in memory were observed in the other behavioral tests over time. Hepatic histopathology, on the 7th d.p.i., revealed necrotic foci surrounded by inflammatory infiltrate, predominantly neutrophils and some lymphocytes. Moreover, inflammatory nodules composed of macrophages, lymphocytes, and giant cells were also observed in the liver of animals with ALI on the 7th d.p.i. No histopathological changes were observed in the brain on the 7th d.p.i. For locomotor and neuroinflammatory analysis, male C57BL/6 WT or TNFR1-/- mice received saline or TAA i.p. After 24 hours, locomotor activity was assessed, and levels of TNF, IFN-γ, IL-6, IL-10, IL-12p70, CCL2, CX3CL1, and BDNF were measured in the prefrontal cortex and hippocampus. The absence of TNFR1 attenuated locomotor deficits, and, in parallel, increased levels of both pro-inflammatory mediators and IL-10 in the brain during ALI-induced HE, on the 1st d.p.i. These data suggest that TNF plays a regulatory role in the development and progression of HE. Despite relative motor and cognitive recovery over time, animals with ALI showed mild to moderate necrotic hepatitis after seven days, indicating persistent hepatic inflammation even after neurological symptom improvement.